(untitled) (TAJ: Journal of Teachers Association, 2009)
Intestinal tuberculosis is still a common abdominal problems in developing countries like us. Sixty cases of intestinal tuberculosis admitted in the surgical wards of Mymensingh Medical College Hospital over 2 years with different presentations have been studied here. All of them under went through surgical procedures for their management. The age range of the patients was 13 to 55 years and most commonly involved age group was 20-40 years. Male to female ratio was 1:1.4. 60% of the patients were in low socio-economic group and 20% of the patients had got the positive history of contact. 60% of the patients presented with chronic intestinal obstruction. The most commonly involved site was lleocaecal region in 51.6% of the patients. Right hemicolectomy with ileotransverse anastomosis was performed commonly 63.3% of the patients but limited resection and stricturoplasty are also safe and effective procedures. doi: 10.3329/taj.v16i1.3899 TAJ June 2003; Vol.16(1): 24-27